(untitled) (Islas, 2025)
Introduction: In today’s hyper-globalized world, designing city brands that align with local identities and the aspirations of urban groups is an essential condition for sustainable urban development. The objective of this study was to determine the foundations for a brand for the five-centuries-old city of Trinidad (Cuba). Methods: The methodology focused on three key aspects: (1) the city as perceived by internal audiences, (2) how it is viewed by external audiences, and (3) the city as projected by the social groups that inhabit it and shape local and national policies. Results: The findings reveal a homogeneous urban identity aligned with aspirations for Trinidad, expanding the range of possibilities for establishing a viable brand consistent with Cuba’s tourism and social model. Conclusions: Although heritage remains the central axis of Trinidad’s cultural identity and sustainable development, there is a strong aspiration to achieve the comprehensive commercialization of the destination, aiming to highlight other local values such as its stunning beaches, natural landscapes, and traditions.